Mengoptimalkan Potensi Siswa melalui Pendekatan Multiple Intelligences dalam Pembelajaran - Auralia, Feby Angel; Ismayani; Lesmana, Gusman (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
Humans as creatures created by Allah SWT have diverse intelligence, which is not limited to intellectual ability as measured through IQ. The Multiple Intelligence Theory proposed by Howard Gardner identifies nine types of intelligence, namely linguistic, logical-mathematical, spatial, kinesthetic, musical, interpersonal, intrapersonal, naturalist, and existential. This research uses descriptive methods to describe the importance of the multiple intelligences approach in education. The results show that learning that is diverse and appropriate to student characteristics can increase motivation, prevent feelings of low self-esteem, and support academic achievement and social-emotional development. Therefore, educators are expected to adapt learning strategies that cover all aspects of intelligence, so that students can reach their maximum potential in the learning process. Success in the real world requires a holistic understanding of intelligence, involving a combination of multiple abilities.